A Study Of Idioms Found In Freedom Writers Movie - Lely Oktaviani; Misnadin Misnadin (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2018)
This study focuses on idioms found in Freedom Writers movie. This study aims to find and explain the types of idioms found in the movie using the theory of types of idioms proposed by Fernando (1996) and the properties of idioms using the theory of properties of idioms proposed by Nunberg, Sag and Wasow (1994). This study employs qualitative design as the research design. In addition, content analysis is applied to obtain the data in which the writer becomes the key instrument of the study. Interactive data analysis, then, is conducted to analyze and explain the data. The data of the study are taken from the characters’ dialogues in Freedom Writers movie. This study shows the findings of the types of idioms and the properties of idioms. In terms of types of idioms, 45 data of idioms were found. The data are classified into three types of idioms: pure idioms (7 data), semi-idioms (10 data), and literal idioms (28 data). Moreover, in terms of properties of idioms, the data are classified into six properties: conventionality (the total 45 data), inflexibility (36 data of the total 45 data), figuration (2 data of the total 45 data), proverbiality (1 datum of the total 45 data), informality (6 data of the total 45 data), and affect (5 data of the total 45 data).